IMPROVING VOCABULARY ABILITY BY USING COMIC IN SMA 1 RUMBIO JAYA - Wida Rianti (Journal of English Language and Education, 2019)
The problems of this research were how to improve vocabulary using comic and how to motivate the students to apply it in their d English. The research was guided by a conceptual framework leading to the using comic through peer work to improve their motivation to speak English during the process of classroom communication interaction. The research type was an action research. The subject consisted of 20 students of the third special class of SMA 1 in Rumbio jaya . The research data were collected using test (test after first treatment and test after the second treatment), observation for collecting data on the students’ motivation in improving vocabulary ability using series pictures. Data on vocabulary ability using comic were analyzed using the descriptive and statistic analysis, to know the improvement in mean students after the first cycle and the second cycle. Based on the first cycle, the students’ average was 67.8, then, on the second treatment, the students’ average increase to be 78.8. It can conclude that teaching vocabulary using comic can improve students’ vocabulary ability.